Congenital adrenal hyperplasia due to P450 oxidoreductase deficiency - Zhang, Jin; Woo, Kwan Leong; Hai, Yongxiong; Wang, Shimin; Lin, Ying; Huang, Ying; Peng, Xiaofang; Wu, HongShi; Zhang, Shaoling; Yan, Li; Li, Yan (Frontiers in Endocrinology, 2022)
Objective: To raise awareness of Cytochrome P450 Oxidoreductase Deficiency (PORD, a rare form of congenital adrenal hyperplasia (CAH), through a case of pregnant woman with virilisation symptoms. Case Description: A 30-year-old Chinese woman was referred to hospital after 7 years of presenting signs of virilisation, including voice deepening, acromegaly, hirsutism, clitoromegaly, and acne. These symptoms appeared since her third gestation. Her second birth died 9 hours after birth and had signs of clitoris hypertrophy. Her third born was a son who presented with flat nose, radius and humerus bone malformation, and small penis at birth. Panel of POR-related genetic tests revealed that the patient carried c.1370 G>A (p.R457H), which is a POR heterozygous gene, while her husband carried a POR heterozygous gene as well, c.1379 C>A (p.S460Y). Two heterozygous mutations of the POR were found in her son: c.1370 G>A and c.1379 C>A. In PORD, c.1370 G>A (p.R457H) was reported as a susceptible gene, while c.1379 C>A (p.S460Y) has not been reported as responsible for the disease so far. Discussion and literature review: PORD is a rare form of CAH and caused by POR gene mutations. Most PORD patients are identified and diagnosed in pediatrics department. Internal medicine and obstetrics physicians are unfamiliar with the disease. As clinical manifestations are diverse, PORD could be easy to miss or to be misdiagnosed.Typical clinical manifestation includes adrenal insufficiency-related symptoms, such as bone malformations and sexual development disorders. PORD is diagnosed through genetic testing. Investigations of steroid metabolic products in urine through gas chromatography-mass spectrometry or liquid chromatography-mass spectrometry are also helpful for the diagnosis, but neither of them are widely available in China. In this case, the patient had a history of infertility, and her third child was born with congenital defect and carried a PORD-related gene. In general clinical practice, if a pregnant woman presents with abnormal virilisation symptoms, CAH possibilities should be considered, including rare causes such as PORD. Conclusion: PORD is a rare autosomal recessive genetic disease. We summarised the clinical characteristics and genotypes that were previously reported in the Chinese population and identified a novel mutation.